1995
DOI: 10.1063/1.360765
|View full text |Cite
|
Sign up to set email alerts
|

The Néel temperature of nanocrystalline chromium

Abstract: Wide-angle neutron diffraction measurements taken at temperatures from 6 to 250 K indicate that the portion of a chromium sample with a mean grain size of 73 nm is antiferromagnetically ordered at temperatures below 100 K. The Néel temperature (about 120±10 K) for this nanocrystalline sample is suppressed considerably below that of strain-free single-crystal chromium (311 K).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 8 publications
0
6
1
Order By: Relevance
“…The reason can be explained that the size distribution of the nanocapsules prepared in the previous work 19 is wider than that of the present nanocapsules and the magnetization of antiferromagnetic phase cannot be detected with a small applied field of 100 Oe. The Néel temperature of chromium nanoparticles with a size of 13 nm vary from 300 to 350 K as reported by Tsunoda et al, 29 and the Néel temperature of 73 nm chromium nanoparticles is 120 K as reported by Fitzsimmons et al 30 However, the Néel temperature of sample E is not observed. This may be ascribed to that the particles are in the superparamagnetic state at the temperature corresponding to the Néel temperature of the bulk chromium.…”
Section: Resultsmentioning
confidence: 57%
“…The reason can be explained that the size distribution of the nanocapsules prepared in the previous work 19 is wider than that of the present nanocapsules and the magnetization of antiferromagnetic phase cannot be detected with a small applied field of 100 Oe. The Néel temperature of chromium nanoparticles with a size of 13 nm vary from 300 to 350 K as reported by Tsunoda et al, 29 and the Néel temperature of 73 nm chromium nanoparticles is 120 K as reported by Fitzsimmons et al 30 However, the Néel temperature of sample E is not observed. This may be ascribed to that the particles are in the superparamagnetic state at the temperature corresponding to the Néel temperature of the bulk chromium.…”
Section: Resultsmentioning
confidence: 57%
“…Here, the particles of Cr are considerably larger and thus, the reason for such large increase in the magnetization of even the 0 h sample with size %60 nm is most likely due to undetected surface oxides. The earlier conflicting results on the magnetization of Cr nanoparticles [11][12][13][14][15] are probably also due to undetectable surface oxides whose magnetization are much larger than that of pure Cr (Figs. 1 and 6).…”
Section: Magnetization Studiesmentioning
confidence: 90%
“…1 and 6). Since Cr is easily oxidized [11,22], it may be difficult to measure the magnetic properties of unoxidized Cr nonoparticles unless proper procedures such as surface coating are used to avoid oxidation. An increase in M with decrease in particle size can also result from the increasing role of uncompensated surface spins in nanoparticles which is more easily detected in the nanoparticles of stable oxides [20,21], ferritin [8] and ferrihydrites [10].…”
Section: Magnetization Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, it has been shown that the two structures are generally not the same. For example, the spin-density wave in a Cr layer can be modified or even suppressed as observed with neutron scattering in nanocrystalline Cr ( Figure 5) [81,82,83], Fe/Cr bilayers [84] and Fe/Cr superlattices ( Figure 6) [34,85], and there are data suggesting that ferromagnetic overlayers can modify the spin-structure of NiO [86,87,88] at the interface. The unambiguous determination of the spin structure in thin films and small particles, both at their interfaces and surfaces as well as in their interior still remains one of the most challenging experimental questions.…”
Section: Magnetic Structurementioning
confidence: 99%